The effect of HIIT vs. SIT on muscle oxygenation in trained sprint kayakers - Paquette, M.; Bieuzen, F.; Billaut, F. (European Journal of Applied Physiology, 2021)
Purpose: To assess the performance change and physiological adaptations following nine sessions of short high-intensity interval training (HIIT) or sprint-interval training (SIT) in sprint kayakers. Methods: Twelve trained kayakers performed an incremental test and 3 time trials (200 m, 500 m and 1000 m) on a kayak ergometer. Oxygen consumption (V.O2) and muscle oxygenation of the latissimus dorsi, biceps brachii, and vastus lateralis were measured. Athletes were then paired for sex and V.O2max and randomized into a HIIT or a SIT training group, and performed nine training sessions before repeating the tests. Results: Training improved performance in HIIT (200 m: + 3.8 ± 3.1%, p = 0.06; 500 m: + 2.1 ± 4.1%, p = 0.056; 1000 m: + 3.0 ± 4.6%, p = 0.13) but changes in performance remained within the smallest worthwhile change in SIT (200 m: + 0.8 ± 4.1%, p = 0.59; 500 m: + 0.5 ± 4.1%, p = 0.87; 1000 m: + 1.3 ± 4.6%, p = 0.57). In the 1000 m, training led to a greater deoxygenation in the biceps brachii and vastus lateralis in HIIT, and in the latissimus dorsi in SIT. In HIIT, the best predictors of improvements in 1000 m performance were increases in latissimus dorsi and vastus lateralis maximal deoxygenation. Conclusion: In a group of trained sprint kayakers, greater improvements in performance can be obtained with HIIT compared with SIT, for any distance. Training did not change V.O2peak, but increased muscle maximal deoxygenation, suggesting both HIIT and SIT elicit peripheral adaptations. Performance improvement in the 1000 m was associated with increased maximal muscle deoxygenation, reinforcing the contribution of peripheral adaptations to performance in sprint kayaking.